Two new species and two new records of deep-water caridean shrimps from Brazil (Decapoda: Pandalidae, Palaemonidae, Crangonidae) - Anker, Arthur; Pachelle, Paulo P.g.; Tavares, Marcos (Zootaxa, 2014)
The present study deals with four species of benthic deep-water caridean shrimps collected on the continental slope off southeastern Brazil, between 360 m and 900 m. The deepwater pandalid Bitias stocki Fransen, 1990, previously known only from a few localities in the eastern Atlantic, is reported for the first time from the western Atlantic (Brazil). The Brazilian material of B. stocki also represents the first record of the genus Bitias Fransen, 1990 in the western Atlantic. The palaemonid Periclimenes tenellus (Smith, 1882), previously known only from South Carolina and New Jersey, USA, is reported for the first time from Brazil, representing a considerable range extension of this uncommon species into the southwestern Atlantic. Another deepwater palaemonid shrimp is described as new: Periclimenes bathyalis sp. nov. The new species is morphologically closest to the echinoid associates Periclimenes milleri Bruce, 1986 and Periclimenes ingressicolumbi Berggren & Svane, 1989. Finally, the bizarre deepwater crangonid genus Prionocrangon Wood-Mason in Wood-Mason & Alcock, 1891 is reported for the first time from Brazil and the southwestern Atlantic, where it is represented by a new species, Prionocrangon brasiliensis sp. nov.